Research on South Tripura's Fisheries Development: Current Situation and Prospects: Strategic Choices - Pradip E; Suman A (Advances in Aquaculture and Fisheries Management, 2024)
Because of the increasing demand for fish, the northeastern state of Tripura's fishing industry is currently undergoing a shift to become a "income-generating enterprise." In order to identify some strategic choices for overall growth, this article sought to analyze the current state and prospects of the fisheries in the southern area of the state. Culture fisheries, which are conducted in small ponds and mini-barrages throughout the district, are the mainstay of fisheries development, according to the study. The area under culture fisheries is 3436 ha, or 97.75% of the district's total water resources, and they contributed more than 99 percent (35,152 MT) of the district's total fish production in 2017–18.Fish production from culture fisheries, fish productivity of culture fisheries, and the compound annual growth rate (CAGR) for culture fisheries resources were found to be 2.420, 4.528, and 1.802, respectively. By 2025, the district would be able to produce 11696 MT of fish with an annual fish productivity of 2893 kg per hectare, according to projections made using the linear pattern of logarithmic time series data. However, by that time, 118 MT of fish would need to be obtained from outside the district, indicating a 4000 MT shortfall from the current level of fish production (2017–18). The amount of fish consumed annually per person exceeds the ICMR guidelines. The study also made an effort to address a number of managerial and technical factors that must be taken into account when developing strategic choices for the development of fisheries in the South Tripu district.